Strategi Penyiaran Efektif Di Media Massa Dan Digital Dalam Perspektif Hadis - A. Fadli; Arifuddin Ahmad; Zulfahmi Alwi; Sumarni Sumai (Jurnal Khabar: Komunikasi dan Penyiaran Islam, 2025)
Mass media broadcasting has a strategic role in shaping public opinion and disseminating information widely. In the perspective of Islamic communication, broadcasting not only functions as a means of communication, but also as a medium to convey messages of truth that originate from the Qur'an and Sunnah. This study aims to analyze effective mass media broadcasting strategies based on the guidance of the hadiths of the Prophet. This study examines how the principles of Islamic communication, such as honesty, clarity, and aesthetics in delivering messages, can be applied in modern broadcasting to increase its impact and effectiveness. The method used is a literature review of relevant hadiths. The results of the study show that effective broadcasting must be oriented towards truth, creativity, and relevance of the message, and use methods that are appropriate to the needs of the audience. Digital technology provides great opportunities to increase audience interaction and involvement, so that messages of goodness can be delivered widely and measurably. In conclusion, the mass media broadcasting strategy based on the perspective of Islamic communication is able to produce message delivery that is not only informative, but also builds moral and spiritual values. This makes mass media broadcasting an important instrument in preaching and the formation of a better society.